Biogeographical variation in specific IgE recognition of temperate and subtropical grass pollen allergens in allergic rhinitis patients. Issue 2 (3rd February 2020) - Kailaivasan, Thina H; Timbrell, Victoria L; Solley, Graham; Smith, William B; McLean‐Tooke, Andrew; van Nunen, Sheryl; Smith, Peter; Upham, John W; Langguth, Daman; Davies, Janet M
Abstract: Objective: Globally, grass pollens (GP) are major aeroallergen triggers of allergic rhinitis (AR) and asthma. However, patterns of allergic sensitisation to pollen of temperate (Pooideae: Lolium perenne ) and subtropical (Chloridoideae: Cynodon dactylon and Panicoideae: Paspalum notatum ) subfamilies in diverse climates remain unclear. This study aims to evaluate the level of allergic sensitisation and IgE specificity for major GP allergens representing the three subfamilies in biogeographically distinct regions. Methods: Participants (GP‐allergic with AR, 330; non‐atopic, 29; other allergies, 54) were recruited in subtropical: Queensland, and temperate: New South Wales, Western and South Australia, regions. Clinical history, skin prick test (SPT), total and specific IgE to GP and purified allergens (ImmunoCAP) were evaluated. Cross‐inhibition of sIgE with Pas n 1, Cyn d 1 and Lol p 1 by GP extracts was investigated. Results: Queensland participants showed higher sensitisation to P. notatum and C. dactylon than L. perenne GP. sIgE was higher to Pas n 1 and Cyn d 1, and sIgE to Pas n 1 and Cyn d 1 was inhibited more by Panicoideae and Chloridoideae, respectively, than Pooideae GP. Conversely, participants from temperate regions showed highest sensitisation levels to L. perenne GP and Lol p 1, and sIgE to Lol p 1 was inhibited more by Pooideae than other GP. Conclusion: Levels and patterns of sensitisation to subtropical and temperate GP in AR patients depended on biogeography. Knowledge of the specificity of sensitisation to local allergens is important for optimal diagnosis and choice of allergen‐specific immunotherapy to maximise benefit. Abstract : Global distributions of grass subfamilies vary with climate and biogeography. Allergic rhinitis patients with grass pollen allergy, exemplified by four Australian climatic regions, showed higher levels of allergic sensitisation and specific IgE cross‐reactivity to pollen allergens of temperate (e.g. Lolium perenne : Lol p 1) or subtropical (e.g. Paspalum notatum : Pas n 1) grasses, depending upon biogeography. Understanding patterns of patient sensitisation to temperate and subtropical grass pollens is critical for optimal diagnosis and formulation of allergen immunotherapy.